Enhancing community potential to boost grassroots economy through value-added pickled bamboo shoots, Thailand - Totum, Boonmee (Edelweiss Applied Science and Technology, 2024)
The objectives of this research article were: 1) to examine the community context, problems, and needs, 2) to enhance the community's capacity through the process of upgrading and adding value to fermented bamboo shoot products, and 3) to assess the capacity development of the Ban Sang Thor community, Phon Mueang Subdistrict, Lao Suea Kok District, Ubon Ratchathani Province. This study employed a mixed-methods research design. The key informants were 12 experts, 50 workshop participants selected through purposive sampling, and ten experts, 50 producers (selected through purposive sampling), and 100 consumers selected through accidental sampling for product development satisfaction evaluation. Data were analyzed using descriptive statistics, including percentages, frequencies, means, and standard deviations. Qualitative data were analyzed using content analysis and descriptive explanations. The Ban Sang Thor community, characterized by a rich historical background and traditional Heet Sip Song Kong Sip Si customs, addressed socioeconomic challenges such as poverty, household indebtedness, and low income through the enhancement of fermented bamboo shoot products. The community engages in educational initiatives regarding hygienic production practices and participates in packaging design processes. The resulting products exhibit durability, aesthetic appeal, and consumer acceptance. High levels of satisfaction from experts and consumers culminate in the production of safe sanitary products with a distinct community-branded identity. Sustainable economic development contributes to the preservation of a community's cultural heritage.